Using theory of consumption values to predict organic food purchase intention: Role of health consciousness and eco-friendly LOHAS tendency - Kose, Sirin G.; Kircova, Ibrahim (CONSEJO SUPERIOR INVESTIGACIONES CIENTIFICAS-CSIC, 2021)
Aim of study: The objective of this study was to investigate the relationship between eco-friendly LOHAS (Lifestyle of Health and Sustainability) tendency, health consciousness, perceived value of organic food and organic food purchase intention in the framework of personality-perception-behavioral intention. Area of study: Turkey. Material and methods: Data were collected from consumers using structured questionnaires. The research model was analyzed with the Partial Least Square Structural Equation Modeling technique. Main results: Results show that eco-friendly LOHAS tendency (beta= 0.292, p<0.01), health consciousness (beta=0.140, p<0.05), emotional value (beta=0.282, p<0.01), and social value (beta=0.099, p<0.05) positively influence intention to purchase organic food, whereas financial value and functional value were not significantly related to intention to purchase organic food. Furthermore, eco-friendly LOHAS tendency and health consciousness are positively related to all dimensions of perceived value of organic food. Research highlights: Findings point out that affective dimension of perceived value of organic food is more considerable than cognitive dimension in a developing country. Emotional value of organic food is more important for consumers who have high level of eco-friendly LOHAS tendency while functional value of organic food is more essential for consumers who a have high level of health consciousness.
Keywords: perceived value; consumer behavior; organic agriculture; ENVIRONMENTAL ATTITUDES; SUSTAINABLE CONSUMPTION; CONSUMER MOTIVATIONS; INDIAN CONSUMERS; LIFE-STYLE; BEHAVIOR; DETERMINANTS; PERCEPTIONS; QUALITY; Agriculture